INVESTIGATION OF THE STUDENTS’ OPINIONS ON VOCATIONAL GUIDANCE SERVICES CONDUCTED AT HIGH SCHOOLS - Ayçiçek, Burak (International Online Journal of Education and Teaching, 2020)
The aim of this study is to analyze different views of students studying at Anatolian high school, industrial vocational high school and private high school about vocational guidance services. The sample of the study consisted of 180 high school students from three different school types. Of them, 103 were male and 77 were female. In the study, survey method was employed and the data were collected through vocational guidance service evaluation questionnaire developed by the researcher. The findings showed that students found the vocational guidance services that provided at school insufficient. In addition, students’ opinions on vocational guidance services were found to differ significantly in terms of gender and school type variables. The students stated their opinions on the importance of vocational guidance services and their main problems, expectations and suggestions related to the vocational guidance services.